Adhesion properties of styrene-butadiene rubber (SBR)/Standard Malaysian Rubber (SMR L)-based adhesives in the presence of phenol formaldehyde resin (eXPRESS Polymer Letters)
The adhesion properties, i. e. viscosity, tack and peel strength of styrene-butadiene rubber (SBR)/Standard Malaysian Rubber (SMR L)-based pressure-sensitive adhesive was studied using phenol formaldehyde resin as the tackifying resin. Toluene was used as the solvent throughout the experiment. SBR composition in SBR/SMR L blend used was 0, 20, 40, 60, 80, 100%. Three different resin loadings, i. e. 40, 80 and 120 parts per hundred parts of rubber (phr) were used in the adhesive formulation. The viscosity of adhesive was determined by a HAAKE Rotary Viscometer whereas loop tack and peel strength of paper/polyethylene terephthalate (PET) film were measured using a Lloyd Adhesion Tester operating at 30 cm/min. Results indicate that the viscosity of adhesive decreases with increasing % SBR whereas loop tack passes through a maximum value at 20% SBR for all resin loadings. Except for the control sample (without resin), the peel strength shows a maximum value at 60% SBR for the three modes of peel tests. For a fixed % SBR, adhesive sample containing 40 phr phenol formaldehyde resin always exhibits the highest loop tack and peel strength, an observation which is associated to the optimum wettability of adhesive on the substrate.